La gestión administrativa de la Importadora Chimasa en la ciudad de Babahoyo - Muñoz Sañay, Ariana Valentina (2021)
The investigation of how the administrative management is carried out within the IMPORTADORA CHIMASA IN THE CITY OF BABAHOYO serves to know what is the strategy used by the manager to be able to correctly solve the problems that arise within the company without it affects its operation. In addition, there are problems such as the lack of training to staff so that they can provide better service to users and thus improve the image of the company, since the person in charge does not want to invest in it, another of the problems that is evident It is the equipment necessary to carry out all the daily tasks that the employees must perform, it was also observed in the same way that the cancellation of salaries is delayed a lot for reasons that are explained in this writing, a decrease in annual sales and the pandemic was also a key reason for sales to suffer this variation significantly in 2020, for the resolution of this project, observation will be used to find the present problems and detail them, in addition to that, for a better understanding, collection is used as a method. of data an interview directed both to the employees who work within it and to the manager in charge to know the s opinions of both parties and based on their statements based on the analysis of the project.